NOVEL ANALYTICAL STUDY FOR REACTION INTERMEDIATES IN THE PRIMARY RADIATION INTERACTION OF DNA USING A SYNCHROTRON RADIATION-INDUCED LUMINESCENCE SPECTROSCOPY. Issue 1 (11th February 2019) - Kojima, T; Aihara, H; Kodashima, Y; Makishima, H; Nakiri, S; Takada, S; Shimada, H; Ukai, M; Ozga, C; Holzapfel, X; Schmidt, Ph; Küstner-Wetekam, C; et al.
Abstract: To identify the precise molecular processes to induce DNA lesions, we attempt a novel spectroscopy of X-ray induced luminescence (XIL) using soft X-ray synchrotron radiation, which is a non-destructive analysis of the reaction intermediates in the elementary reaction pathway of damage induction and self-organized restoration. Using a liquid micro-jet technique to introduce aqueous samples in a vacuum chamber, we measure UV-visible luminescence from nucleotide solution as a function of the soft X-ray energy from the nitrogen to oxygen K-edge region. The XIL intensities for the nucleotide solutions are significantly enhanced in the soft X-ray region (410–530 eV) which is ascribed to the K-shell excitation/ionization of nitrogen atoms in the nucleobases. Furthermore, the XIL spectra do not show any signature of X-ray absorption near-edge structure (XANES) of the nucleobases. This is because the luminescence intensities collected from the integral area of the micro-jet only reflect the quantum yield of luminescence of the absorbed X-ray into UV-visible light irrespective of the absorption cross sections, i.e. of XANES. Thus the present result is the first evidence of luminescence as a result of X-ray absorption of aqueous nucleotides.